Vibration Problems ICOVP-2007 - 0nan, Esin.; Sengupta, Dipak.; Banerjee, Muralimohan.; Mukhopadhyay, Basudeb.; Demiray, Hilmi. (Springer Proceedings in Physics,, 2009)
This volume presents the Proceedings of the 8th International Conference on Vibration Problems, held from 30 January 2007 to 3 February 2007, in Howrah, Kolkata, West Bengal, India. As with the earlier conferences in the ICOVP series, the purpose of ICOVP-2007 was to bring together scientists with different backgrounds, actively working on vibration-related problems of engineering both in theoretical and applied fields. The main objective did not lie, however, in reporting specific results as such, but rather in joining and exchanging different languages, questions and methods developed in the respective disciplines, and to thus stimulate a broad interdisciplinary research. The topics, indeed, cover a wide variety of vibration-related subjects. Audience: Scientists, researchers and graduate students in Physics and Engineering